Performance of Angora goats, mohair production, and farmer income in extensive livestock systems of north Patagonia, Argentina - Sacchero, Diego Mariano; Gonzalez, Ezequiel Bernardo; Maurino, Maria Julia; Lopez, Miriam; Cortes, Maria Victoria; Alvarez, Rocio De Los Angeles; Bidinost, Franca (Frontiers Media, 2023)
Introduction: In Argentina, mohair production is limited exclusively to the Patagonia region. This activity takes place under different biophysical conditions and with marked seasonality in the climatic conditions and productivity of natural grasslands. The present study aimed to analyze Angora goat performance, mohair production, and income in two contrasting environments of northern Patagonia.